Remdesivir for COVID-19 in Indonesia : A Case Series - Gembong Satria Mahardhika; Theodore Dharma Tedjamartrono; Haidar Zain; Efriadi Ismail (Respiratory Science, 2021)
To date, COVID-19 still gives rise to a high mortality rate in Indonesia. The definitive therapy has yet to be found. However, some medications are said to be potential in subduing the infection, e.g. remdesivir. United States, Japan, and some countries in Europe had use remdesivir against severe COVID-19 infection. In Indonesia, no study has shown to discuss remdesivir therapy for severe COVID-19. This case series shows the first five remdesivir usages in severe COVID-19 patients in RSDC Wisma Atlet Kemayoran, Jakarta. In this retrospective case series, we include the first five severe COVID-19 patients that got remdesivir plus standard therapy in Rumah Sakit Darurat COVID-19 Wisma Atlet Kemayoran, Jakarta in October 2020. Five patients who got remdesivir in this case series experienced clinical and laboratory improvement. The ventilation and oxygenation status, as well as PF ratio and the neutrophils-lymphocytes ratio (NLR), got better. The possible side effect of remdesivir usage, renal function impairment, was not seen in these patients. At last, the five patients were discharged home with negative swab results, three until seven days after remdesivir therapy finished. Remdesivir therapy for COVID-19 in this case series is associated with a good outcome. Compassionate use of remdesivir should be considered in severe COVID-19. However, a bigger sample of randomized control trial needs to be done to show the effectiveness of remdesivir against COVID-19.